FLAVONOID DARI KULIT BATANG AKWAY (Drimys beccariana, Gibbs) DAN AKTIVITAS SITOTOKSIK TERHADAP SEL KANKER PAYUDARA T47D - Tati Herlina; Apriani Sulu Parubak (BRIN Publishing, 2019)
Flavonoid compounds obtained from natural products could reduce the risk of cancer. Akway plants (Drimys beccariana, Gibbs) are endemic plants in the Papuan highlands, especially in Manokwari. D. beccariana has been widely used in traditional medicine in West Papua. This study aims to determine the cytotoxic activity of flavonoid from D. beccariana bark against T47D breast cancer cells. Pure compound form isolation was characterized using UV and IR spectrophotometers, and tested cytotoxic activity against T47D breast cancer cell using the Sulforodamine B. method. The D. beccariana stem bark (2.5 kg) was extracted with methanol solvent which was then partitioned with n-hexane and ethyl acetate solvents. Ethyl acetate fraction was separated and purified by column chromatography method to yield pure compound (7.1 mg). The UV-Vis spectrum of pure compound showed two bands at λmax 287 (I) and 205 nm (II), as well as the addition of AlCl3 shifting reagents with the addition of 7 and 5nm wavelengths, specific to the -OH and C=O groups in flavonoid compound. The infrared spectrum of pure compound (KBr) showed the presence of –OH stretch (3422 cm-1), C=O (1659 cm-1), C= C aryl (1463 cm-1), and C-O (1060 cm-1) which is typical for flavonoid. The pure flavonoid compound obtained from the of D. beccariana bark showed cytotoxic activity against T47D breast cancer cells with IC50 values of 3.2 µg/mL. D. beccariana is a promising source of breast anticancer agents.